2019
DOI: 10.1021/acs.inorgchem.9b01288
|View full text |Cite
|
Sign up to set email alerts
|

Selective Self-Assembly of a Rectangular Ruthenium Supramolecule from an Unsymmetrical Bridging Unit

Abstract: Herein, we report the synthesis of an unsymmetrical diruthenium bridging unit containing a multidentate oxamate ligand and the subsequent formation of a rectangular supramolecule. The reaction of oxamate 1, 2-((4-bromo-2,6dimethylphenyl)amino)-2-oxo-acetic acid, and [(p-cymene)RuCl 2 ] 2 affords a novel unsymmetrical diruthenium acceptor clip 2, where two ruthenium metal centers are ligated with either [O,O] or [N,O].The molecular clip 2 and bipyridine donor selfassemble to form two-dimensional rectangular sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…), due to the stretching vibrations of the triflate anions. These assignments are well documented in literature [67][68][69] and support the formation of the cationic assemblies as their triflate salts. ESI-MS analysis further supports the formation of metallarectangles 2c, 2d, 3c, and 3d.…”
Section: Synthesis and Characterisationsupporting
confidence: 83%
“…), due to the stretching vibrations of the triflate anions. These assignments are well documented in literature [67][68][69] and support the formation of the cationic assemblies as their triflate salts. ESI-MS analysis further supports the formation of metallarectangles 2c, 2d, 3c, and 3d.…”
Section: Synthesis and Characterisationsupporting
confidence: 83%
“…Some studies have reported the successful growth of crystals at temperatures as low as −20 °C. [ 37–38 ]…”
Section: Slow Diffusion/layering Methodsmentioning
confidence: 99%
“…Some studies have reported the successful growth of crystals at temperatures as low as −20 °C. [37][38] With both methods, if a sufficient quantity of the sample is present, performing different sets of experiments simultaneously using different solvent combinations is highly recommended as it increases the success rate and saves time. If crystals are not formed within weeks, all samples should be gathered, and other solvent combinations should be tried.…”
Section: Slow Diffusion/layering Methodsmentioning
confidence: 99%
“…These structures have been complexed with appropriate multidentate ligands to form metallocycles and metallocages with guest-inclusion ability. [29][30][31][32][33][34][35][36][37][38][39][40] The sizes of the resulting metallocycles and metallocages are strategically adjusted by changing the size of the linkers and the length and shape of the ligand.…”
Section: Introductionmentioning
confidence: 99%
“…Dinuclear arene ruthenium, in which two piano‐stools are joined with anilato, oxalato or related bis‐bidentate linkers, have also been reported. These structures have been complexed with appropriate multidentate ligands to form metallocycles and metallocages with guest‐inclusion ability [29–40] . The sizes of the resulting metallocycles and metallocages are strategically adjusted by changing the size of the linkers and the length and shape of the ligand.…”
Section: Introductionmentioning
confidence: 99%